Examining diffusion to understand the how of SASA!, a violence against women and HIV prevention intervention in Uganda - Elizabeth Starmann (BMC Public Health, 2018)
Abstract Background A growing number of complex public health interventions combine mass media with community-based “change agents” and/or mobilisation efforts acting at multiple levels. While impact evaluations are important, there is a paucity of research into the more nuanced roles intervention and social network factors may play in achieving intervention outcomes, making it difficult to understand how different aspects of the intervention worked (or did not). This study applied aspects of diffusion of innovations theory to explore how SASA!, a community mobilisation approach for preventing HIV and violence against women, diffused within intervention communities and the factors that influenced the uptake of new ideas and behaviours around intimate partner relationships and violence. Methods This paper is based on a qualitative study of couples living in SASA communities and secondary analysis of endline quantitative data collected as part of a cluster randomised control trial designed to evaluate the impact of the SASA! intervention. The primary trial was conducted in eight communities in Kampala, Uganda between 2007 and 2012. The secondary analysis of follow up survey data used multivariate logistic regression to examine associations between intervention exposure and interpersonal communication, and relationship change (n = 928). The qualitative study used in-depth interviews (n = 20) and framework analysis methods to explore the intervention attributes that facilitated engagement with the intervention and uptake of new ideas and behaviours in intimate relationships. Results We found communication materials and mid media channels generated awareness and knowledge, while the concurrent influence from interpersonal communication with community-based change agents and social network members more frequently facilitated changes in behaviour. The results indicate combining community mobilisation components, programme content that reflects peoples’ lives and direct support through local change agents can facilitate diffusion and powerful collective change processes in communities. Conclusions This study makes clear the value of applying diffusion of innovations theory to illuminate how complex public health intervention evaluations effect change. It also contributes to our knowledge of partner violence prevention in a low-income, urban East African context. Trial registration ClinicalTrials.gov #NCT00790959. Registered 13th November 2008.